PENGARUH ELEMEN PEMBENTUK INTELLECTUAL CAPITAL TERHADAP KINERJA KEUANGAN PERUSAHAAN PERBANKAN (Students' Journal of Accounting and Banking, 2013)
The purpose of this study was to examine the effect of the elements principal Intellectual Capital is measured by the Value Added Intellectual Coefficient (VAICTM), which has a component of Value Added Capital Employed, Value Added Human Capital and Structural Capital Value Added to the company's financial performance is proxied by Return on Assets and return On Equity. The object of this study is a banking company listed on the Indonesia Stock Exchange in 2007-2011. Sampling technique in this study using purposive sampling method, we obtained 105 samples of observational data from 21 banking companies listed in Indonesia Stock Exchange during the years 2007 to 2011. In the present study examined the effect of Intellectual Capital (VAICTM) and the three elements of the financial performance by using multiple regression analysis. The results showed that there is a positive influence on Intellectual Capital (VAICTM) and the constituent elements of Value Added Capital Employed, Structural Capital Value Added to the financial performance of Return on Assets and Return On Equity. For the Human Capital Value Added element there is no effect on return on assets, but there are negative influences Value Added Human Capital on Return On Equity. Keywords: Intellectual Capital (VAICTM), Value Added Capital Employed, Value Added Human Capital, Structural Capital Value Added, Return on Assets, Return On Equity.